Dissemination of technology Training for teachers of SMAN Kembangbahu in managing synchronous online learning - Ratna Nurdiana; Sutarum; Hadi Suryanto (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The purpose of the synchronous online learning management training is to improve the skills of teachers in implementing face-to-face online learning. The training method uses the in-out method. This means that it is done face-to-face and online so that training participants experience online learning directly guided by a mentor. Participants are teachers at SMAN Kembangbahu as many as 42 people. During the training, many participants were initially still not used to using online learning procedures to the fullest, such as the procedure for being present 10 minutes before online learning, turning on the participant's camera, asking for readiness, asking questions and interacting. After participating in the training, participants realized that implementing a good procedure actually made it easier for teachers to carry out learning. The importance of managing synchronous online learning made the participants very enthusiastic during the training.